Intimate invocations : Al-Ghazzī's biography of ʻAbd al-Ghanī al-Nābulusī (1641-1731) - Ghazzī, Muhạmmad ibn Muhạmmad, 1760-1799. (Islamic History and Civilization, 2012)
Despite the growing interest in the intellectual history of early modern Arabs and Ottomans, many key figures of the period remain unknown. In this unique biographical account, edited and published here for the first time, Muḥammad Kamāl al-Dīn al-Ghazzī (1760-1799), the chief Shafi'i jurisconcult of Damascus, introduces us to one of the leading figures of early modernity, 'Abd al-Ghanī al-Nābulusī (1641-1731). Being al-Nābulusī's great grandson, al-Ghazzī had direct access to the family's collective memory through his parents and grandparents, as well as to his great grandfather's scattered memoirs. Written about fifty years after al-Nābulusī's death, al-Ghazzī's biography, al-Wird al-Unsī, remains the authoritative account of the great master's distinguished career, covering many aspects of his life and work in breadth, depth, and sophistication unmatched by any of the competing biographies.